Fiscal politics - Gaspar, Vitor; Gupta, Sanjeev; Mulas-Granados, Carlos (Washington, D.C International Monetary Fund (IMF), 2017)
​Two main themes of the book are that (1) politics can distort optimal fiscal policy through elections and through political fragmentation, and (2) rules and institutions can attenuate the negative effects of this dynamic. The book has three parts: part 1 (9 chapters) outlines the problems; part 2 (6 chapters) outlines how institutions and fiscal rules can offer solutions; and part 3 (4 chapters) discusses how multilevel governance frameworks can help. ( from Amazon page)
Introduction 1. Fiscal policy / Vitor Gaspar, Sanjeev Gupta, Carlos Mulas-Granados Part I Elections, Ideology, and political fragmentation 2. Governments and promised fiscal consolidations: do they mean wat they say? / Sanjeev Gupta, Joao Tovar Jalles, Carlos Mulas-Granados and Michela schena -- 3. Fiscal policy over the election cycle in low-income countries Christain Ebeke and Dilan Olcer -- 4. Economic and political determinations of tax policies in OECD countries / Mark Hallerberg and Jurgen van Hagen -- 5. Now or later? the political economy of public investment in democracies / Sanjeev Gupta, Estelle X. Liu, and Carlos Mulas-Granados -- 6. Do elections affect the wage bill? / Yehenew Endegnaneu, Mauricio Soto, and Genevieve Verdier -- 7. Energy subsidies and public social spending: theory and evidence / Christian Ebeke and Constant Lonkeng Ngouana -- 8. Its politics, stupid! political constrains determine governments reactions on the great recession / Fabian Gunzinger and Jan-Egbert Sturm -- 9. Fragmented politics and public debt / Ernesto Crivelli, Sanjeev Gupta, Carlos Mulas-Granados, and Carolina Correa-Caro -- Part II Institutions, Rules, and fiscal councils 10. Political Institutions, state building, and tax capacity: crossing the tipping point / Vitor Gaspar, Laura Jaramillo, and Philippe Wingender -- 11. Fiscal Discipline and exchange rates: does politics matter? / Joao Tovar Jalles, Carlos Mulas-Granados and Jose Tavares -- 12. Expenditure rules: effective tools for sound fiscal policy? / Till Cordes, Tidiane Kinda, Priscilla Muthoora, andAnke Weber -- 13. Fiscal rules to tame the political budger cycle: evidenve from Italian Municipalities / Andrea bonfatti and Lorenzo Forni -- 14. On the determinants of fiscal noncompliance: an empirical analysis of Spanish regions / Mar Delgado-Teller, VictorD. Lledoand Javier J. Perez -- 15. Budger Institutions in low-income countries / Sanjeev Gupta, Sami Ylaoutinen, Brian olden, holger van eden -- 16. Fiscal watchdogs and sound fiscal policy: is the barking loud enough to tame politicians? / Xavier debrun, Marc Gerard, and Jason Harries -- Part III Supranational fiscal politics 17. The making of a continental financial system: lessons for Europe from early American history / Vitor Gaspar -- 18. Fiscal politics in the Euro Area / Luc Eyraud, Vitor Caspar, and Tigran Pogbosyan -- 19. IMF conditionality and revenue performance / Ernesto Crivelli and Sanjeev Gupta --
Includes bibliographical references and index
Keywords: Public finance; FISCAL POLICY; BUDGETS; POLITICS; POLITICAL ECONOMY; ELECTIONS; POLITICAL SCIENCE; ECONOMIC ASPECTS